Inflammatory cytokines and metabolic responses to high-intensity intermittent training: Effect of the exercise intensity - Rhibi, Fatma; Zouhal, Hassane; Lira, Fabio Santos [UNESP]; Ouerghi, Nejmeddine; Prioux, Jacques; Besbes, Sophia; Tijani, Jed M.; Hackney, Anthony C.; Abderrahman, Abderraouf Ben (Termedia Sp. z.o.o., 2022)
To examine the effects of two high-intensity intermittent training (HIIT) programs of varying intensities (100% vs. 110% of maximal aerobic velocity [MAV]) on metabolic, hormonal and inflammatory markers in young men. Thirty-seven active male volunteers were randomly assigned into: HIIT experimental groups (100% MAV [EG100, n = 9] and 110% MAV [EG110, n = 9]) and a control groups (CG100, n = 9 and CG110, n = 9). Particpants performed high intesity intermittent exercise test (HIIE) at 100% or 110% MAV. Venous blood samples were obtained before, at the end of HIIE and at 15 min of recovery, and before and after 8 weeks of HIIT programs. After training, Glucose was lower (p < 0.01) in EG100 (d = 0.72) and EG110 (d = 1.20) at the end of HIIE, and at 15 min recovery only in EG110 (d = 0.95). After training, Insulin and Cortisol were lower than before training in EG100 and EG110 at the end of HIIE (p < 0.001). After HIIT, IL-6 deceased (p < 0.001) in EG100 (d = 1.43) and EG110 (d = 1.56) at rest, at the end of HIIE (d = 1.03; d = 1.75, respectively) and at 15 min of recovery (d = 0.88;d = 1.7, respectively). This decrease was more robust (p < 0.05) in EG110 compared to EG100. After HIIT, TNF-α deceased (p < 0.001) in EG100 (d = 1.43) and EG110 (d = 0.60) at rest, at the end of HIIE (0.71 < d < 0.98) and at 15 min of recovery (0.70 < d < 2.78). HIIT with 110% MAV is more effective in young males on the improvements of some metabolic (Glucose), hormonal (Cortisol) and inflammatory (IL-6) markers at rest, at the end of HIIE and 15 min of recovery than training at 100% MAV.
Keywords: Endurance; Inflammatory parameters; Intermittent exercise; Interval training